2008
DOI: 10.1186/1476-069x-7-54
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to mobile telecommunication networks assessed using personal dosimetry and well-being in children and adolescents: the German MobilEe-study

Abstract: Background: Despite the increase of mobile phone use in the last decade and the growing concern whether mobile telecommunication networks adversely affect health and well-being, only few studies have been published that focussed on children and adolescents. Especially children and adolescents are important in the discussion of adverse health effects because of their possibly higher vulnerability to radio frequency electromagnetic fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 36 publications
1
71
1
2
Order By: Relevance
“…There have been several reports that non-thermal levels of RF radiation can increase apoptosis in response to ionizing ultra-violet or gamma radiation [42,43]. Studies investigating whether such synergism extends to exposure to multiple radio frequencies have been few, and their results, like ours, negative, whether epidemiological [2,3] or experimental [4][5][6][7]. In the present case, the absence of significant effects may have been due in part to the low specific absorption rates employed (< 0.3 W/kg except in the pituitary glands of group 3) and the use of just a single exposure period rather than repeated exposures.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…There have been several reports that non-thermal levels of RF radiation can increase apoptosis in response to ionizing ultra-violet or gamma radiation [42,43]. Studies investigating whether such synergism extends to exposure to multiple radio frequencies have been few, and their results, like ours, negative, whether epidemiological [2,3] or experimental [4][5][6][7]. In the present case, the absence of significant effects may have been due in part to the low specific absorption rates employed (< 0.3 W/kg except in the pituitary glands of group 3) and the use of just a single exposure period rather than repeated exposures.…”
Section: Discussionmentioning
confidence: 48%
“…The few studies there have been in this area have not clearly identified potential health risks related to multiple RF exposure: no relationship has been established between multifrequency exposure and cellular alterations in embryos during gestation [2], alteration of testicular function [3], toxic or carcinogenic effects [4,5], or chronic symptoms such as headaches or sleep alterations in adults [6] and children [7]. Nevertheless, the paucity of information on the possible bio-effects of multiple RF signals contrasts with the concern of the general public and of various governmental entities [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…We have compared results obtained from our measurement campaign with those reported by similar studies [23,25,26].…”
Section: Comparison With Similar Measurement Campaignsmentioning
confidence: 74%
“…Therefore to derive more reliable EMF mean values per technology and environment the obtained measurement samples need post-processing. The postprocessing of the obtained results in the present study are based on the method described in [23]. To classify the exposure, all measurement values below the detection limit were replaced by half of the limit values before analysis (e.g., all detection values of 0.05 V/m were replaced with the value 0.025 V/m).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation